Balloon-borne observation of Aitken nuclei in the Antarctic stratosphere and troposphere - Ito, T.; Kanazawa, I. (1985)
Aitken nuclei (0.002 or = r or = 0.1 microns in the atmosphere are produced through gas-to-particle conversion processes, and they grow in size by heterogeneous nucleation processes and others to produce larger aerosol particles. In the study of global background aerosol pollution, full knowledge of such aerosol processes in the clean atmosphere is essentially required. In this sense, it is important to examine the behavior of aerosols in a clean atmosphere which is not contaminated directly by aerosols and gases emitted from the Earth's surface. The Antarctic atmosphere is thought to be such a clean atmosphere. From an extensive surface observation of aerosols carried out at Syowa Station (69 deg 00'S, 39 deg 35'E) Antarctica, it has been revealed that various phenomena relating to long-range transport of trace constituents and/or photochemical processes resulting in production or growth of aerosol particles are clearly observed in Antarctica. This paper gives a preliminary report of observations made by balloon-borne Aitken nuclei sonde in 1983, at Syowa Station.